Effect of substance use disorder on anxiety, depression and quality of life in adolescents - Mustafaoğlu, Rüstem; Kaya Mutlu, Ebru; Mutlu, Caner; Çiftçi, Arzu; Razak Özdinçler, Arzu (Journal of Dependence, 2020)
Objective: The aim of this study was to compare the anxiety, depression and quality of life levels of substance use disorder adolescents with their healthy peers. Method: A total of 95 volunteers, including 60 males who received inpatient treatment in the substance addiction service, and 35 healthy individuals who were gender and age matched were included in the study. The anxiety, depression and quality of life of the participants were questioned and recorded using face-to-face interview method. Results: Substance use disorder adolescents were found to be statistically significantly higher in the State Anxiety Sub-Scale, Trait Anxiety Sub-Scale and Beck Depression Scale scores compared to their healthy peers. In addition, it was found that there was a statistically significant decrease in substance use disorder adolescents compared to their healthy peers in all areas of the Children’s Quality of Life Scale, except for the social functionality score. Conclusion: Anxiety and depression levels of substance use disorder adolescents were higher than their healthy peers, and their quality of life levels were lower.